Sensitivity optical non-linear measurement based on wide-band phase objects - Shao, Zhangyang; Yang, Yong; Yang, Junyi; Zhou, Wenfa; Liu, Kun; Li, Zhongguo; Fang, Yu; Wu, Xingzhi; Song, Yinglin (Frontiers in Materials, 2023)
A modified high sensitivity optical nonlinear measurement technique with an absorptive homemade phase object (HPO) is reported in order to characterize the value of weak nonlinear refraction material. The absorptive HPO used in this technique is two transparent glass plates on which a liquid film between two pieces of transparent glasses is deposited and added a rotating object at the below HPO to modulate the phase of a PO. Results show that the measuring sensitivity can be improved by changing the transmittance of the absorptive HPO. Meanwhile, because the phase retardation of HPO can be continuously adjustable by modulate the rotating object, it makes the sensitivity of measurement at different wavelengths of laser optimal. Furthermore, the modified technique can be used to measure the spectrum of nonlinear refraction coefficients of materials at the continuous wavelength. This method further expands the 4f phase coherent imaging measurement technology, not only solves the deficiencies of the conventional phase object, but also improves the accuracy of the measurement. Experiment and theoretical analysis results are presented to validate our technique.